(untitled) (Environment & Health, 2025)
The aim of the work. To follow and analyze the life and creative path of Professor Max Joseph von Pettenkofer from a student to the President of the Bavarian Academy of Sciences and the organizer and director of the first Institute of Hygiene in Europe. Materials and methods. Available printed materials were used - textbooks, manuals and electronic resources - biographical articles, Wikipedia materials, search methods, bibliosemantic historical, analytical, descriptive. Results of the study. The creative and life path of Max Pettenkofer is traced with an emphasis on his role in the development of hygienic science. The contribution of Max Pettenkofer’s scientific research, covering a wide range of chemical and hygienic problems in the formation of the experimental direction of hygienic research and the development of hygienic diagnostic methods, which brought him worldwide recognition as a scientist as the founder of modern experimental hygiene and preventive medicine, is shown. It was determined that the principles and methods of hygienic diagnostics, founded more than a century and a half ago by Max Pettenkofer as a special system of thinking, synthesis, analysis and actions aimed at studying the factors of the human life environment (biological, chemical, physical and social), the state of human health (at the individual and population level) and establishing the relationship between the influence of factors of this environment on the health of the population, remain relevant and require further implementation in the development of a new «architecture» of the health care system at different levels of management.